A new age within MIS 7 for the Homo neanderthalensis of Saccopastore in the glacio-eustatically forced sedimentary successions of the Aniene River Valley, Rome. (1st December 2015) - Marra, Fabrizio; Ceruleo, Piero; Jicha, Brian; Pandolfi, Luca; Petronio, Carmelo; Salari, Leonardo
Abstract: Field observations as well as borehole, sedimentological and geochronologic data allow us to reconstruct the geologic setting of the Aniene River Valley in northern Rome, framing it within the recently recognized picture of temporally constrained, glacio-eustatically forced aggradational successions of this region. The sedimentary successions cropping out in this area include those described in the literature of the early 20th century in Saccopastore, where two skulls of Homo neanderthalensis were recovered. Based on the geometry, elevation and sedimentologic features of the investigated sedimentary deposits, the stratigraphic record of Saccopastore is correlated with the aggradational succession deposited in response to sea-level rise during glacial termination III at the onset of MIS 7 (i.e. ∼250 ka), corresponding to the local Vitinia Formation, as opposed to previous correlation with the MIS 5 interglacial and a locally defined "Tyrrhenian" stage (∼130 ka). This previous attribution was based on the interpretation of the sedimentary succession of Saccopastore, occurring between 15 and 21 m a.s.l., as a fluvial terrace formed around 130 ka during the Riss-Würm interglacial, ca. 6 m above the present-day alluvial plain of the Aniene River. In contrast to this interpretation, a 40 Ar/ 39 Ar age of 129 ± 2 ka determined for this study on a pyroclastic-flow deposit intercalated in a fluvial-lacustrine sequence forming a terrace ∼37 m a.s.l. near the coast of Rome constrains the aggradational succession in this area to MIS 5, precluding the occurrence of an equivalent fluvial terrace at lower elevation in the inland sector of Saccopastore. We therefore interpret the stratigraphic record of Saccopastore as the basal portion of the aggradational succession deposited in response to sea-level rise during MIS 7, whose equivalent fluvial terrace occurs around 55 m a.s.l. in this region. We also review the published paleontological and paleoethnological records recovered in Saccopastore and demonstrate their compatibility with the faunal assemblages and lithic industries occurring in the sedimentary deposits of the Vitinia Formation, while we show the lack of any unequivocal Late Pleistocene (MIS 5) affinity. We therefore propose that the chronostratigraphic position of the Saccopastore deposits containing the two skulls should be around 250, 000 years, as opposed to a previously preferred age of 130, 000 years. The revised age makes these skulls the oldest Italian occurrences of H. neanderthalensis and provides evidence for a substantially coeval appearance and evolutionary path with respect to central-northern Europe. Highlights: We revise chronostratigraphy of the Saccopastore site hosting two skulls of Homo neanderthalensis . We constraint the MIS 5 fluvial terraces in Rome by means of a 40 Ar/ 39 Ar age of 129 ± 2 ka. We show that the Saccopastore succession does not correlate with MIS 5 as previously thought. We demonstrate that the Saccopastore succession deposited 250 ka at the onset of MIS 7. The revised age makes those in Saccopastore the oldest Italian remains of H. neanderthalensis .